Weak impact of tourism activities on biodiversity in a subterranean hotspot of endemism and its implications for the conservation of cave fauna. Issue 3 (31st October 2014) - Faille, Arnaud; Bourdeau, Charles; Deharveng, Louis; Didham, Raphael; Ribera, Ignacio
Abstract La Verna chamber (France, western Pyrenees), the largest underground chamber in France, hosts 18 species of endemic hypogean invertebrates, all highly modified (troglobitic). It was recently opened for tourism activities. To estimate the risks incurred by its fauna in this new environmental context, we conducted a 3‐year survey of the terrestrial fauna of the cave, focusing on the four steno‐endemic species of beetles present. We established five sampling spots in the chamber that were monitored every 3 to 4 months during 3 years. Our results did not detect any negative impact of the tourism activity on cave biodiversity. Neither the number of observed specimens nor the species richness decreased in the control spots. The huge size of the chamber is assumed to prevent significant microclimatic changes and the presence of very large boulders and cracks is assumed to offer plenty of suitable spaces, which allow invertebrates to escape local disturbance and illumination. In spite of the high vulnerability of cave organisms, disturbance of cave habitats does not necessarily result in biodiversity decrease, if the cave disturbance is limited in duration, intensity, and spatial coverage with respect to the cave size.